PENGEMBANGAN E-COMMERCE DAN INOVASI PRODUK PISANG MENJADI STICK PISANG PEKON YOGYAKARTA KECAMATAN GADING REJO KABUPATEN PRINGSEWU - Betty Magdalena; Viola De Yusa (Institut Informatika dan Bisnis Darmajaya, 2019)
Pekon Yogyakarta is into 3 hamlets and the majority of the population is mostly working as farmers. In addition, there are some UKM run by citizens such as SMEs Banana, UKM Geblek and UKM Bricks and tile. UKM Geblek and Bricks less suitable to be developed further, both in terms of product development, finance, and marketing. UKM Banana itself has not been developed maximally when this UKM is very potential to be developed further, because the lack of knowledge of the community about business development and product innovation in entrepreneurship where bananas can be processed into Stick, so the potential is not developed and tend to static. For that in the devotion activities in Pekon Yogyakarta, we try to help develop UKM Banana into Stick both in terms of product, finance, and marketing. In Pekon Yogyakarta itself does not yet have a village and e-commerce website so that the marketing of products from Pekon Yogyakarta is still done manually and it needs to hold training on computers and the internet for local residents in order to use and utilize technology to provide information and communication. So needed a website-based information system in order to support village government officials in providing information and e-commerce to promote the product to the wider community. Along with the development of technology and information, means of promotion is done through the internet. So that can be accessed where and whenever we are.Keywords: E-Commerce, UKM Stick Banana, Pekon Yogyakarta